SELEÇÃO DE FUNGOS FILAMENTOSOS PRODUTORES DE β-GLICOSIDASES: PRODUÇÃO, CARACTERIZAÇÃO BIOQUÍMICA E SUA APLICAÇÃO NA HIDRÓLISE DE BIOMASSA - Almeida, Janaina Marques de (2014)
Microbial ?-glucosidases have received great attention in recent years due to its wide spectrum of biotechnological applications, including the bioethanol production, the aroma improvement in wine processes and the juice industry, the oligosaccharides and glycoconjugates synthesis, and others. In this study, selection of filamentous fungi producers of ?-glucosidase and waste inducers of this enzyme was performed, nine fungal species and three agro-industrial: passion fruit peel, coffee husk and canola meal, waste were tested. After selection, the effect of various physicochemical parameters on ?-glucosidase production by the fungus Penicillium verruculosum and Trichoderma viride was investigated, using passion fruit peel waste and canola meal as substrates. The ?-glucosidases were characterized biochemically and enzyme extracts were used in the process of passion fruit peel saccharification, in order to maximize the glucose release. The experiments were carried out using a central composite rotational design applicable to the response surface methodology. The simulation data was conducted to assist in obtaining the optimum factors. Among the evaluated fungal strains, P. verruculosum produced the highest levels of ?-glucosidase, when grown in the passion fruit peel presence. Maximum production levels have been achieved when the culture medium was adjusted to pH 4.2, the concentration of the substrate was 2.9 % and the cultivation time was 8.6 days, corresponding to 8.54 U mL?¹. The highest rates of glucose release from the passion fruit peel hydrolysis were obtained by applying the T. viride crude extract. The best hydrolysis conditions were established as 96 hours of incubation, at 60ºC, pH 5.0 and enzyme concentration equivalent to 22.5 U g?¹ of substrate. The passion fruit peel is shown a promising raw material for the production of ?-glucosidases as well for the glucose production by enzymatic hydrolysis due to be a low cost material and generated in large quantities in juice industries. In addition, the ?-glucosidases produced by both fungi show interesting properties, such as thermostability and glucose tolerance, which favors their applications in various industrial processes.